2010
DOI: 10.1002/ana.22164
|View full text |Cite
|
Sign up to set email alerts
|

Amantadine use associated with impulse control disorders in Parkinson disease in cross‐sectional study

Abstract: A recent controlled clinical trial suggested a role for amantadine as a treatment for pathological gambling in patients with Parkinson disease (PD). Analyzing data from a large cross-sectional study of impulse control disorders (ICDs) in PD, amantadine use (n = 728), vs no amantadine use (n = 2,357), was positively associated with a diagnosis of any ICD (17.6% vs 12.4%, p < 0.001) and compulsive gambling specifically (7.4% vs 4.2%, p < 0.001). This amantadine association remained after controlling for covariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
89
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(94 citation statements)
references
References 18 publications
4
89
0
1
Order By: Relevance
“…A post-hoc analysis of a large multi-centred epidemiological study showed a significant association between amantadine use and ICBs (17.6% of patients on amantadine vs. 12.4% of those not on amantadine) (Weintraub et al, 2010b). More studies are necessary to determine the exact effect amantadine has on ICBs because it is already used in PD and is known to have a beneficial effect on motor symptomatology.…”
Section: Discussionmentioning
confidence: 99%
“…A post-hoc analysis of a large multi-centred epidemiological study showed a significant association between amantadine use and ICBs (17.6% of patients on amantadine vs. 12.4% of those not on amantadine) (Weintraub et al, 2010b). More studies are necessary to determine the exact effect amantadine has on ICBs because it is already used in PD and is known to have a beneficial effect on motor symptomatology.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a large cross-sectional study of ICB, amantadine use was associated with a higher incidence of at least one active ICB when compared to no amantadine use. 33 In addition to ICB-specific measures, the CBTbased intervention also seemed to benefit depression and anxiety, which are commonly reported comorbidites, 6 as well as measures relating to work and social function. These findings are in keeping with a conceptual model which makes dysphoria a central component of PD-ICB.…”
Section: Executive Dysfunctionmentioning
confidence: 99%
“…4,7 However, an important unanswered question is whether PD itself confers an altered risk for ICDs. Preliminary comparison studies suggest that ICDs are more common in treated PD patients than in healthy controls (HCs).…”
mentioning
confidence: 99%